The tyranny of distance and the gravity of resources - Robertson, Peter E.; Robitaille, Marie-Claire (Wiley, 2017)
To what extent does geography remain an important determinant of comparative advantage and factor incomes in resource markets? We estimate gravity models for resources and find that some minerals and fuels, particularly Iron Ore and Gas, do have very high elasticities of trade with respect to distance. To assess the implications of this we then consider a simple counterfactual where location advantages are eliminated. We find that for a few countries, including Australia and New Zealand, distance barriers have a large impact of their market share.